Developing Speaking E-Book: A Supplementary Material for Teaching Recount Text to Tenth Graders - Rhima Holida Nurmala; Nur Mukminatien; Francisca Maria Ivone (Graduate School of Universitas Negeri Malang, 2023)
The development of the Speaking e-book in this study was carried out because students and teachers of the tenth grade of Senior High Schools needed supplementary material to study recount text which focuses more on speaking activities and these activities can bridge the gaps in the textbook and workbook. The product was developed based on the model of Research and Development proposed by Borg and Gall (1996). From the process of product validation and tryout, some results showed that the Speaking e-book was effective to be used as supplementary material to teach recount text since the series of tasks provided helped develop students’ speaking ability.